Probability Constrained Load Flow on the Basis of Tracing Method - Irina Golub (Acta Energetica, 2015)
In order to control the electric power system operation it is important to know the sensitivity of random state variables to disturbances and the factors affecting the sensitivity of the variables to ensure feasible ranges of their changes. The stochastic problem of electric power system control is solved iteratively and is reduced to successively solving the equivalent deterministic problems, including determination of numerical characteristics of the variables by the methods of probabilistic load flow. To minimize the number of controls it is suggested to use the tracing method in each step of the deterministic equivalent method. The presented numerical results demonstrate the high performance of the suggested approach.